Компьютерный анализ электромеханических напряжений в полиэтиленовой изоляции силового кабеля при наличии микровключений - Кучерявая, И.Н. (Технічна електродинаміка, 2012)
As applied to polymer insulation of extra-high voltage power cable, the distributions of volume electric force and connected with the force mechanical stress in the zone of separate water microinclusion and inclusion with treeing channel are studied. The qualitative patterns and quantitative estimations for the values of electric force and maximum von Mises stress are obtained for microinclusions of different sizes. The mathematical model and computer program are developed to determine electric force and mechanical stress in polyethylene taking into account structural defects filled with water as well as to simulate the mechanism of destructive action on inhomogeneous insulating material.